1997
DOI: 10.1046/j.1471-4159.1997.69010266.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of β‐Amyloid Peptide Is Promoted by Membrane Phospholipid Metabolites Elevated in Alzheimer's Disease Brain

Abstract: Abstract:Increased amounts of /3-amyloid (Aj3) peptide deposits are found in Alzheimer's disease brain. These amyloid deposits have been implicated in the pathophysiology of this common dementing illness. A/li peptides have been shown to be toxic to neurons in cell culture, and this toxicity is critically dependent on the aggregation of the peptide into cross-/li-pleated sheet fibrils. Also, in vivo and postmortem NMR studies have shown changes in certain brain membrane phospholipid metabolites in normal aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 43 publications
1
6
0
2
Order By: Relevance
“…The NMR PDE findings have been confirmed by classical neurochemical analyses of AD brain which also demonstrate elevated levels of GPC (14). Previous light scattering studies demonstrated that GPC enhances Ab aggregation (15). The present study examines by fluorescence spectroscopy the interaction of Ab and GPC with the intact erythrocyte membrane to determine a possible pathophysiological role for elevated levels of GPC in AD.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The NMR PDE findings have been confirmed by classical neurochemical analyses of AD brain which also demonstrate elevated levels of GPC (14). Previous light scattering studies demonstrated that GPC enhances Ab aggregation (15). The present study examines by fluorescence spectroscopy the interaction of Ab and GPC with the intact erythrocyte membrane to determine a possible pathophysiological role for elevated levels of GPC in AD.…”
Section: Introductionsupporting
confidence: 71%
“…In our earlier work, aggregation of Ab was measured by a light scattering method (absorption at 400 nm) (15). This methodology is based on measuring the turbidity due to insoluble, aggregated Ab (26).…”
Section: Discussionmentioning
confidence: 99%
“…The intensities of these biomarkers do not show significant changes over time in the TERT transgenic group. Interestingly, some of the metabolites identified here (ie, sphingomyelin, glycerophosphoethanolamines) have been previously linked to neurodegenerative disorders and various aspects of aging and disease (Klunk et al 1997; Cutler & Mattson 2001). …”
mentioning
confidence: 91%
“…An age-related change has been detected in asymmetric membrane cholesterol distribution [82]. Similarly, a progressive increase in phospholipid metabolite formation has been observed during aging, which is accelerated in AD [83]. Elevation of membrane phospholipid metabolites may play a role in the deposition of Ai, as some of these metabolites are known to increase the aggregation of Ai.…”
Section: Control Of Membrane Properties By Cholesterolmentioning
confidence: 95%